On Minimal dense Sets and its Applications - Sharmistha Bhattacharya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The aim of this paper is to introduce a new concept of  dense set and to study its topological structure. It can be shown that the collection of all this  - dense set forms a supra topological space if  is introduced. Also the concept of minimal  dense set is introduced and some of its applications are shown. Lastly introducing the concept of  sub maximal space various important properties of minimal  dense sets are studied in a - sub maximal space.